2015
DOI: 10.1021/ic502745u
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of CO2 Activated on Transition Metals and Sulfur Ligands

Abstract: Dicationic dicarbonyl [Ru(bpy)2(CO)2](2+) (bpy = 2,2'- bipyridyl) exists as equilibrium mixtures with [Ru(bpy)2(CO)(COOH)](+) and [Ru(bpy)2(CO)(CO2)](0) depending on the pH in H2O. Those three complexes work as the precursors to CO, HCOOH production, and CO2 carrier, respectively, in electro- and photochemical CO2 reduction in aqueous solutions. However, [Ru(bpy)2(CO)2](2+) loses the catalytic activity toward CO2 reduction under aprotic conditions because [Ru(bpy)2(CO)2](2+) is not regenerated from [Ru(bpy)2(C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…Transition-metal atom, ion, metal clusters as well as metallic oxides that could convert this gas into valuable chemicals have attracted much attention. In particular, metal ions, serving as a prototypical model of heterogeneous catalysis, with CO 2 have been studied extensively. Bohme and co-workers reported detailed results of the transition-metal ions react with CO 2 in the gas-phase. They found that only nine transition-metal ions can get O from CO 2 at room temperature, with lots of heat released, but others can only form M + (CO 2 ) complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Transition-metal atom, ion, metal clusters as well as metallic oxides that could convert this gas into valuable chemicals have attracted much attention. In particular, metal ions, serving as a prototypical model of heterogeneous catalysis, with CO 2 have been studied extensively. Bohme and co-workers reported detailed results of the transition-metal ions react with CO 2 in the gas-phase. They found that only nine transition-metal ions can get O from CO 2 at room temperature, with lots of heat released, but others can only form M + (CO 2 ) complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, two carbonyl stretching frequencies in the newly prepared dicarbonyl complex were observed at 2060 and 1995 cm −1 in the IR spectra (Figure S1). These values are 30-40 cm −1 lower than those of similar Ru complexes ([Ru(N-N) 2 (CO) 2 ] 2+ ; N-N = bidentate pyridyl ligands) [11][12][13]. The reason is that the reduction of the azo moiety increases the electron density of the complex, resulting in a red shift of the CO bands [5].…”
Section: Synthesis and Characterization Of The Diradical Complexmentioning
confidence: 78%
“…Bipyridine analogues function not only as supporting ligands for stabilizing metal complexes, but also as electron pool sites. For example, in addition to catalysts for the production of useful resources, such as in multi-electron reductions of carbon dioxide and water-gas shift reactions [4][5][6][7][8][9][10][11], bipyridine analogues are also utilized as photosensitizers [12] and phosphorescence materials [13]. A variety of studies that imparted selectivity to various reactions by strictly controlling the coordination sphere have been reported for many ruthenium complexes.…”
Section: Introductionmentioning
confidence: 99%